Design of a conductive material detection system - Silaban, Freddy Artadima; Budiyanto, Setiyo; Silalahi, Lukman Medriavin (Institute of Advanced Engineering and Science, 2020)
The development of technology and industry development in the 4.0 era is very fast along with these developments in the control of production results such as medicine, food, and safety must be faster and more accurate. To face free trade and global economic competition, every company is required to produce products that have good quality by the standards. By using an experimental method which is the development of this study aims to make a conductive material detector (metal detector) for the pharmaceutical industry, the food industry, and security as compared to using conductive material sensors that are integrated with the Arduino microcontroller. Application testing is carried out to find out whether the Blynk application on an android smartphone with Blynk on a Debian server that has been made previously runs well or not and the alarm system testing uses a buzzer and LED to detect conductive material passing through. Conductive sensor test results showed that the instrument can detect 6 conductivity materials such as stainless steel, aluminum, steel, zinc, copper, and tin. The average response time to detect conductive material is 3 seconds, the average ADC value of the conductive material is 0.55. The test results also successfully send information and data to the Blynk application so that it can be monitored online.